2012
DOI: 10.1002/anie.201105127
|View full text |Cite
|
Sign up to set email alerts
|

The Diaryl(oxy)methyl Group: More than an Innocent Bystander in Chiral Auxiliaries, Catalysts, and Dopants

Abstract: Either as the free alcohol or deprotonated, a carbinol residue bearing gemial, identical aryl residues can at first sight be recognized as an achiral structural unit. When incorporated, however, into a chiral molecule, the two aryl groups become diastereotopic. Thus, they might contribute to an enhancement in stereoselectivity and do so in a variety of reactions. This Minireview highlights developments in stereochemistry when the diaryl(oxy)methyl group is involved, with emphasis given to the beneficial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 208 publications
0
16
0
Order By: Relevance
“…Thus, the role of this component may not simply be steric, an effect that has been previously documented for gemdiaryl groups. 21 In the final stage of catalyst evaluation, the role of the hydroxyl group was examined. Matsumura's work had previously shown that the deoxy-picoline derivative 24 catalyzed the asymmetric hydrosilylation of N-phenyl ketimine 25 but led to poor selectivity compared to the parent catalyst 23, inferring the need for a hydrogen bond to effectively coordinate with the ketimine substrate, leading to the commonly accepted model shown.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the role of this component may not simply be steric, an effect that has been previously documented for gemdiaryl groups. 21 In the final stage of catalyst evaluation, the role of the hydroxyl group was examined. Matsumura's work had previously shown that the deoxy-picoline derivative 24 catalyzed the asymmetric hydrosilylation of N-phenyl ketimine 25 but led to poor selectivity compared to the parent catalyst 23, inferring the need for a hydrogen bond to effectively coordinate with the ketimine substrate, leading to the commonly accepted model shown.…”
Section: Resultsmentioning
confidence: 99%
“…As exemplified in Figure 1, bis-benzylic oxyalkyl groups are a prominent structural motif found in pharmaceutically active compounds, 11 complex natural products 11 and asymmetric catalysts. 12 As such, we expect that this new C–H bond arylation strategy will find broad application across a variety of fields that rely on organic molecule construction. …”
mentioning
confidence: 99%
“…Further control experiments provided useful insights of the process (Scheme 5). Use of syn and anti ‐ 1 j , each delivered conjugate addition product ( 5 ja ) exclusively, which clearly suggests that gem ‐diaryl group at C5 played a pivotal role and is indispensable [26] for the overall γ‐functionalization or β,γ‐annulation of enones, which even cannot be tweaked with a gem ‐aryl/alkyl combination. Interestingly, retro‐cascade process seemed to be operating at a much faster rate than conjugate addition as no 3 a′a′ could not be detected for reaction showed in Scheme 5 b.…”
Section: Methodsmentioning
confidence: 99%